Ruralidade e desproteção social: um retrato da comunidade do Ribeirão Chupé - Rocha, Wysney Pereira (Universidade Federal do Tocantins, 2023)
Social inequalities generate poverty conditions that are not only expressed in the urban environment, but also in rural areas, which are often invisible to social policies and the professional performance of some sectors. Such practices are also consolidated through the naturalization of social inequalities, which is why a critical reading of social phenomena is necessary. Considering these aspects, the work in question aims to discuss the access to social policies in interface with ruralities and aims to understand how the naturalization of poverty is configured as a factor of exclusion from access to social rights of the residents of the Ribeirão Chupé community. As a methodological strategy, we used historical, qualitative, and field research. The research was carried out with the camped community that lives on the banks of the Ribeirão Chupé river, located on the TO-050 highway, between the cities of Palmas and Porto Nacional. Currently, 15 families live in this community. The research instrument adopted was the semi-structured interview, which was configured as a resource for working with oral history. For data treatment we created analysis categories, which were interpreted based on history. As results, we highlight that social policies by themselves are not able to promote social equality; it is necessary to overcome their logic of ensuring the minimum and move towards a new form of sociability. Furthermore, it is necessary to adopt a critical perspective in the work of the professionals who will attend the populations in rural contexts, respecting and knowing the territoriality and the historicity of the work contexts. There is still the need for many discussions and popular involvement so that we can follow paths to fight and overcome poverty, in the same way it is increasingly necessary that we do not naturalize the social phenomena that surround the consolidation of our society, and the historical past that still marks black, indigenous, peasant, LGBTQIA+ populations, among many others.